Construction of Cationic Azahelicenes: Regioselective Three‐Component Annulation Using In Situ Activation Strategy. (26th October 2020) - Wang, Zhishuo; Jiang, Linfeng; Ji, Jinwen; Zhou, Fulin; Lan, Jingbo; You, Jingsong
Abstract: Described herein is a strategy to construct cationic azahelicenes through the three‐component annulation reaction of isoquinoline, indole, and 1, 2‐dichloroethane (DCE), in which DCE serves as an in situ activating agent for C1−H activation of isoquinoline, a vinyl equivalent, and a solvent. This in situ activation annulation reaction features a facile one‐step synthesis and complete regioselectivity. The complete regioselectivity of C1 over C3 for the isoquinoline ring paves a path to the helical structure in a highly ordered sequence. One of the synthesized ionic [5]azahelicenium fluorophores exhibits the potential to serve as a mitochondria‐targeted biomarker with good photostability and low cytotoxicity. Abstract : A three‐component annulation reaction of (iso)quinoline, indole, and 1, 2‐dichloroethane in one step affords a family of cationic azahelicenes. This in situ activation protocol features a facile one‐step synthesis and complete regioselectivity.